-3p-4+4p+8=x

Simple and best practice solution for -3p-4+4p+8=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3p-4+4p+8=x equation:


Simplifying
-3p + -4 + 4p + 8 = x

Reorder the terms:
-4 + 8 + -3p + 4p = x

Combine like terms: -4 + 8 = 4
4 + -3p + 4p = x

Combine like terms: -3p + 4p = 1p
4 + 1p = x

Solving
4 + 1p = x

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 1p = -4 + x

Combine like terms: 4 + -4 = 0
0 + 1p = -4 + x
1p = -4 + x

Divide each side by '1'.
p = -4 + x

Simplifying
p = -4 + x

See similar equations:

| r+10=22 | | 2b-10=b | | 25x+15y=305 | | 9x+11x=180 | | B=2b-10 | | 5abcdefg=6abcdefg-2a+3b | | 10x^3+2y=0 | | 12x+2x=7 | | 0=64x^2-36 | | 2x+y=X | | 6x+9=4x-7 | | a(abc)= | | 63=x-27 | | 7x+16y=11 | | x+37=91 | | (3b-6)+(4b-6b+10)= | | p+(2p+15)+(p+15)=360 | | 16x^2+9=5 | | .15+.2m=.55 | | 1+4v+6v=-19 | | 6*[5*(3*3*3-17)]= | | 3w-9=36 | | 3(y+7)=4(y-7) | | (2y-1)(2y+4y-3)= | | x-6=89 | | 6In(3x)=8 | | -6x+6(5x+5)=-90 | | x=1.34*(x-90000) | | x=1.3*(x-90000) | | x=1.33*(x-90000) | | 10=14-x | | 14x+8y=22 |

Equations solver categories